Association of the severity and progression rate of periodontitis with systemic medication intake - Batista Cárdenas, Daniela (2024)
Background/Purpose: Information on the systemic medication profiles of patients with periodontitis is limited. Therefore, this retrospective cross-sectional study aimed to analyze the relationship between the severity and rate of progression of periodontitis and systemic medication intake using a database of patients who attended the Clinic of Periodontics of the Faculty of Dentistry of the University of Costa Rica. Methods: Electronic health records of patients diagnosed with periodontitis based on the Classification of Periodontal and Peri-Implant Diseases and Conditions (2017) were evaluated. Individuals were further categorized based on the severity (stage) and rate of progression (grade). Data extracted from the patient records included age, sex, and self-reported medication intake. Results: In total, 930 records were included. Most of the studied population was middle-aged (36–64 years old); 43.01% were male, and 56.99% were female. Four hundred and fifty-seven patients (49.14%) reported taking at least one systemic medication for a chronic condition. Regarding the periodontal treatment phase, 62.37% underwent steps 1-3, and 37.63% underwent step 4. The most common systemic medications taken were for cardiovascular diseases (42.28%), followed by medications for diabetes (14.46%) and neurologic disorders (14.46%). Most patients (59.35 %) were diagnosed with Stage III periodontitis. Grade B (48.28%) was the most prevalent. Calcium channel blockers demonstrated a disease severity-dependent association with the periodontal stage (p=0.021). In addition, systemic medications for diabetes mellitus were associated with periodontal disease severity and rate of progression (all Ps <0.05). Conclusions: This study provides indirect evidence of the association between systemic diseases and periodontitis. The positive association between medications used to treat diabetes and the severity and rate of progression of periodontitis may be due to the underlying disease rather than the medications per se.